Controlling the Diameter of Electrospun Yttria‐Stabilized Zirconia Nanofibers. Issue 9 (3rd June 2016) - Koo, Ja Yang; Hwang, Sangyeon; Ahn, Minwoo; Choi, Mingi; Byun, Doyoung; Lee, Wonyoung
Abstract : This work reports the precise diameter control of electrospun yttria‐stabilized zirconia (YSZ) nanofibers from 200 to 900 nm after calcination. Fabricated YSZ nanofibers showed porous nanocrystalline structures with high aspect ratios of more than 500:1 and high surface‐to‐volume ratios with a specific surface area of 43.32 m 2 /g. The diameter of the YSZ nanofibers increased with the viscosity of the precursor solution, which was controlled by the concentrations of either polymers (polyacrylonitrile) or ceramic precursors (YSZ). We present a modified correlation between the diameter of a nanofiber and the synthetic conditions, as the observed behavior for calcined ceramic nanofibers deviated from the expected behavior. Our results demonstrate a modified but simple approach to fabricate ceramic nanofibers with desired diameters, providing a new design guideline for many electrochemical applications.